Pengaruh Pendidikan Matematika Realistik Indonesia Terhadap Pemahaman Konsep Siswa Pada Materi Untung dan Persentase Untung - Sari, Ayudia Permata (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2014)
This study was a quasi-experimental research .The design of study using the One- Shot Case Study aimed to determine whether there is a realistic mathematics education Indonesian influence on students' understanding of the concept of profit and profit percentage in class VII SMP 9 Palembang. Subject of this research is class VII .5 SMP 9 Palembang academic year 2013/2014, amounting to 29 students. Collection and analysis of data on students 'understanding of concepts in the form of a test that contains questions profit and profit percentage that has been adapted to the students' understanding of the concept indicator. Tests carried out after using the approach of Indonesian Realistic Mathematics Education (posttest). Based on the analysis, obtained t-value is 23.71, while the T-table is 1.70. Thus, the t-value is greater than the t-table, so H0 is rejected and Ha accepted. It can be concluded that there are significant Indonesian realistic mathematics education to students' understanding of the concept of profit and profit percentage in class VII SMP 9 Palembang. DOI: https://doi.org/10.22342/jpm.8.2.1862.1-19